Jeunesse et Changement Social : Vers Une Action Concertée en Algérie - Sadouni, Tewfik; Tighedine, Hassina (جامعة محمد خيضر بسكرة - كلية العلوم الإنسانية والاجتماعية, 2020)
Statistics in Algeria declare that every year 14,000 new social movements are launched in Algeria. Indeed, the majority of social movements in Algeria are supervised by the young category which claims recognition of their social status and their share of responsibilities in the decisions of their regions in particular. However, the main causes of these triggers are still linked to lack of information in the first place and the lack of public communication in the second place. Indeed, the social change that comes from social movements always has a characteristic of an abrupt change. This change can have harmful effects on the social and economic stability of society. For this, our communication will therefore be accentuated on the role of public consultation by lover and downstream in the control and supervision of social change in Algeria.
Keywords: القضايا الإجتماعية -- المتغيرات الإجتماعية -- قضايا الشباب -- الجزائر